Explorer le familier comme un « nouveau terrain » - Julitte Huez; Gilles Monceau (Éducation et Socialisation)
The article proposes to consider the professional tensions and institutional contradictions experienced by teacher-researchers (TEs) as "new ground" that is both familiar and little explored scientifically. While there is a great deal of research on higher education, very little takes into account the fact that the researchers who have conducted it are involved in its subject matter. These surveys are often conducted from a stance of distancing which excludes from the analysis the experience and professional background of their authors, who are also involved in the profession. After identifying and comparing certain publications on the subject, we shall report on a socio-clinical investigation based on the experience of a GEASE (Groupe d'entraînement à l'analyse des situations éducatives) conducted with a group of novice teacher-researchers on the one hand, and on collective interviews conducted with teacher-researchers from different institutions, disciplines, status and gender on the other. Two feedback sessions involving GEASE and group interview participants completed the system.